2013
DOI: 10.1016/j.jalgebra.2013.01.001
|View full text |Cite
|
Sign up to set email alerts
|

j -Multiplicity and depth of associated graded modules

Abstract: Let R be a Noetherian local ring. We define the minimal j-multiplicity and almost minimal j-multiplicity of an arbitrary R-ideal on any finite R-module. For any ideal I with minimal j-multiplicity or almost minimal j-multiplicity on a Cohen-Macaulay module M, we prove that under some residual assumptions, the associated graded module gr I (M) is Cohen-Macaulay or almost Cohen-Macaulay, respectively. Our work generalizes the results for minimal multiplicity and almost minimal multiplicity obtained

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(60 citation statements)
references
References 25 publications
5
55
0
Order By: Relevance
“…. , x i ), 0 ≤ i ≤ d − 1 [25]. By the weak Artin-Nagata property AN − d−2 , one has that J i : I ∞ = J i : I = J i : x i+1 and (J i : [29].…”
Section: Lemma 21 Let D ⊆ B ⊆ a And D ⊆ C ⊆ A Be Finite Modules Ovementioning
confidence: 97%
See 1 more Smart Citation
“…. , x i ), 0 ≤ i ≤ d − 1 [25]. By the weak Artin-Nagata property AN − d−2 , one has that J i : I ∞ = J i : I = J i : x i+1 and (J i : [29].…”
Section: Lemma 21 Let D ⊆ B ⊆ a And D ⊆ C ⊆ A Be Finite Modules Ovementioning
confidence: 97%
“…Besides the application in intersection theory and singularity theory, these invariants are also used in the study of the arithmetical properties, like the depth, of the blowup algebras such as the associated graded rings (see for instance, [27,25,21]). …”
Section: Introductionmentioning
confidence: 99%
“…A similar formula for ideals of analytic spread ℓ(I) = s that satisfy condition G s (see Section 3) is given in the following theorem. In [24], the authors defined an R-ideal I of analytic spread ℓ(I) = d to be of minimal j-multiplicity if the ideal I in Proposition 2.2 is of minimal multiplicity, i.e., I 2 = x d I. They proved that this property is well-defined, i.e., that for general elements x 1 , x 2 , .…”
Section: Preliminariesmentioning
confidence: 99%
“…The j-multiplicity has been a very active research topic in the last few years as several results for m-primary ideals have been shown to hold for arbitrary ideals if the Hilbert-Samuel multiplicity is replaced by the j-multiplicity. For instance, numerical criteria for integral dependence (Rees' criterion, [9]), combinatorial interpretation of the multiplicity of monomial ideals ( [16]), and the relation with the Cohen-Macaulayness of blowup algebras ( [21], [24]) have been generalized this way.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation